The Impact of Laisser-Faire Style Leadership on Administrative Performance: the Case of Tanzanian Organizations - Sajilan, Sulaiman; Zandi, GholamReza; Suleiman, Ibrahim; Amin, Mohammad Mohammad (International Journal of Engineering and Technology, 2018)
This study investigated the Impact of Leadership style on Administrative Performance in Tanzanian Organizations. In many organizations, leadership through employee’s commitment is regarded as the key to administration performance to well-functioning, hence leading to attaining goals and objectives of organizations. The objectives of this study were to analyze the impact of Democratic, Laisser-faire and Bureaucratic Styles of Leadership on administrative performance in Zanzibar to understand the influence of autocratic leadership styles on administrative performance. A survey was designed and data collected by dissemination of a questionnaire to a sample size of 120 respondents from Zanzibar, Tanzania. These respondents were selected using random sampling and purposive sampling and data collected was analyzed by the latest Statistical Package for Social Sciences (SPSS) software. The leadership style of democratic, laisser-faire, transactional and transformational leadership styles had a significant positive relationship with staff commitment in the organizations. The laisser-faire and transformational leadership style significant positive association with staff commitment would enhance the productivity and profitability in organization.